2004
DOI: 10.1007/s00216-004-2877-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of pentafluorophenyl hydrazine derivatives to the analysis of nabumetone and testosterone in human plasma by liquid chromatography?atmospheric pressure chemical ionization?tandem mass spectrometry

Abstract: Two carbonyl compounds, nabumetone and testosterone, were derivatized with pentafluorophenyl hydrazine (PFPH) and analyzed by atmospheric-pressure chemical-ionization mass spectrometry. The PFPH derivatives underwent dissociative electron capture in negative-ion APCI (ECAPCI) and gave intense [M-20](-) ions in the mass spectra. In positive-ion APCI, the PFPH derivatives underwent efficient protonation and gave intense [M + H](+) ions in the mass spectra. In CID, the major product ions of the [M-20](-) ions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…All the tested compounds presented a neutral loss of 181 amu (C 6 F 5 N) among other ions. This type of fragmentation was previously observed in other studies when analyzing pentafluorobenzylhydroxylamine PFBHA38, 39 and PFPH derivatives of carbonyl compounds 32, 33. Neutral loss scans were performed in order to confirm the previous results and 19 of the 24 compounds under study were detected under neutral loss scanning of 181 amu.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…All the tested compounds presented a neutral loss of 181 amu (C 6 F 5 N) among other ions. This type of fragmentation was previously observed in other studies when analyzing pentafluorobenzylhydroxylamine PFBHA38, 39 and PFPH derivatives of carbonyl compounds 32, 33. Neutral loss scans were performed in order to confirm the previous results and 19 of the 24 compounds under study were detected under neutral loss scanning of 181 amu.…”
Section: Resultssupporting
confidence: 77%
“…Derivatization of the carbonyl groups was adapted from other studies32, 33 and was performed as follows: 200 µl of 100 m M PFPH in methanol was added to 600 µl of a carbonyl solution (maximum carbonyl functional group concentration level was 1 m M ) and the mixture was left to react for 18 h at room temperature. Extending the reaction time over 18 h was tested on four compounds (A1, A6, K1 and K5) but did not show any significant improvement in terms of signal intensity.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the product ions and collision energies for the derivatized estrogens were identical to the underivatized ones (Table 2). The position of the corona discharge needle and its current were critical in the electron‐capture process;17, 35 the intensity increased as the current increased. However, the maximum discharge current of the mass spectrometer (TSQ 7000) was 10 µA, and the corona probe position fixed.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the earlier reports employ liquid-liquid extraction (LLE) using n-hexane-dichloromethane (Sheen and Her, 2004), diethyl ether (Nobilis et al, 2004) and ethyl acetate (Kobylinska et al, 2003), except for the work of Nobilis et al (2003), where they carried out sample preparation with SPE as well as LLE. The recoveries obtained with SPE in the present study were not quantitative but were consistent and reproducible.…”
Section: Methods Developmentmentioning
confidence: 99%
“…In another report (Nobilis et al, 2004), they identified and determined phase II nabumetone metabolites by HPLC with photodiode array and mass spectrometric detection. A method for simultaneous determination of nabumetone and testosterone in human plasma after derivatization with pentafluorophenyl hydrazine has been presented (Sheen and Her, 2004). The analysis was done by liquid chromatography-atmospheric pressure-chemical ionization mass spectrometry (LC-APCI-MS) in the positive and negative ionization modes, but the run time achieved in their study was too high to be used for routine sample analysis.…”
Section: Introductionmentioning
confidence: 99%